Degradação de biomassa de levedura empregando processos oxidativos avançados químicos e eletroquímicos - Silva, Lilia Ribeiro da [UNIFESP] (2015)
Biological materials have been widely used as biosorbent metals, organometallic and organic compounds successfully.However, the final destination of waste after sorption is a problem to be solved. The main destinations of these materials are incineration, encapsulation in concrete and the deposit in landfills,all of them have harmful consequences to the environment and/or require constant control. Perhaps, this limitation is one of the reasons why biological materials are not incorporated as tools for the treatment of water and wastewater by sanitation companies. Whereas, alternatives to conversion of material employed as biosobent in species little or nothing harmful to the environment could be a way to expand the applications of bioremediation processes for water and waste treatment technology. This work proposed the use of advanced oxidation processes (AOP) as an alternative to degradate yeast biomass from alcohol industry (YB), employed as biosorbents by Applied Chemical Analysis Laboratory (AQUA) UNIFESP. Studies using Fenton and photo-Fenton procedures allowed the elimination of around 72% of the initial mass of the YB, setting a promising alternative for the treatment of solid waste biosorbent.The best condition set for the Fenton degradation was 25 mg YB in 60 min, 800 mgL-1of H2O2 and 40 mgL-1 of Fe2+, whereas for the photo-Fenton process were used these conditions associated with UV lamp action 30W. The applied theoretical model multivariate adaptive regression splines (MARS) was able to describe the experimental data with average error of 2.5% while the error predicted by the experimental design stood at 7.7%. Both errors are adequately considered low, especially considering that the degradation process took about a solid, complex and heterogeneous matrix.